2018
DOI: 10.1186/s12887-018-1151-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of testicular microlithiasis in patients with hypospadias: a retrospective study

Abstract: BackgroundIt has been described that the incidence of testicular microlithiasis is high in several congenital disorders which may be associated with testicular impairment and infertility. Several reports have shown that a prepubertal or pubertal hormonal abnormality in the pituitary-gonadal axis was identified in some patients with hypospadias that is one of the most common disorders of sex development. However, exact prevalence or risk factors of testicular microlithiasis in patients with hypospadias have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
5
0
10
Order By: Relevance
“…Nakamura et al reported that a risk factor for testicular microlithiasis in patients with HS was concomitant UDT [26], which was also found to be a risk factor for high serum FSH in the current study. They found that the incidence of TM in patients with and without UDT was 43.8% and 9.5%, respectively, which was similar with the incidence of high serum FSH in those with and without UDT (58.3% or 7.5%, respectively) in the present study.…”
Section: Discussionsupporting
confidence: 74%
“…Nakamura et al reported that a risk factor for testicular microlithiasis in patients with HS was concomitant UDT [26], which was also found to be a risk factor for high serum FSH in the current study. They found that the incidence of TM in patients with and without UDT was 43.8% and 9.5%, respectively, which was similar with the incidence of high serum FSH in those with and without UDT (58.3% or 7.5%, respectively) in the present study.…”
Section: Discussionsupporting
confidence: 74%
“…An ultrasound examination of his testes revealed mild-to-moderate reduction in size (right: 3.0 × 1.1 cm; left: 2.9 × 1.3 cm) and volume (right: 7.6 mL; left: 8.4 mL) with bilateral segmental testicular microlithiasis ( Fig. 1D ), which may be indicative of degeneration of the testicular parenchyma [ 21 ]. While he claimed to have a normal libido as well as sexual function, semen analysis revealed oligospermia with a decreased mobility rate ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…(1) También existe una clara correlación entre la MT y la infertilidad, siendo la obstrucción por los cálculos en los túbulos seminíferos el factor clave que causa la infertilidad al ocasionar una inflamación secundaria y aumentar la presión intraseminifera, afectando el suministro de sangre a los testículos. (6) La MT está formada por depósitos intratubulares que consisten en núcleos centrales calcificados rodeados por múltiples capas concéntricas de residuos celulares, glicoproteína y colágeno dentro de los túbulos seminíferos. Sin embargo, los posibles mecanismos fisiopatológicos que conducen a la formación de núcleos centrales calcificados de MT aún no se conocen completamente.…”
Section: Discussionunclassified
“…Recientemente, se ha demostrado que organismos similares a las bacterias de tamaño nanométrico (nanobacterias) participan en el proceso de calcificaciones patológicas que se detectaron en muestras de semen de pacientes con MT y pueden causar también quistes en el epidídimo. (2,6,(10)(11)(12)(13) La terminología "nanobacterias" (NB) se refiere a organismos similares a bacterias de tamaño nanométrico, descubriéndose por primera vez en un cultivo celular y nombrada por Kajander y Cifcioglu. (11) Se autoreplican y tienen un tamaño de 0.1 a 0.5 μm.…”
Section: Discussionunclassified
See 1 more Smart Citation